Visible-Light Photoredox-Catalyzed Cascade Reaction for the Synthesis of Pyrrolo[2,1-a]isoquinoline-Substituted Phosphonates - Wang, Lingna; Ma, Tiancong; Qiao, Mingming; Wu, Qiangxian; Shi, Deqing; Xiao, Wenjing (Synthesis, 2019)
A visible-light photoredox-catalyzed oxidation/[3+2] cycloaddition/oxidative aromatization cascade reaction of [(3,4-dihydroisoquinolin-2(1H)-yl)methyl]phosphonates and activated olefins or alkynes for the efficient synthesis of potentially biological active pyrrolo[2,1-a]isoquinoline-substituted phosphonates was developed. This transformation features mild reaction conditions (i.e., visible light irradiation, room temperature), molecular oxygen (O2) as a green oxidant, simple ‘one-pot’ operation.
Keywords: visible light catalysis; [3+2] cycloaddition; pyrrolo[2,1-a]isoquinoline; phosphonate; cascade reaction